Using conversation analytic methods to assess fidelity to a talk-based healthcare intervention for frequently attending patients. (June 2018) - Barnes, Rebecca K.; Jepson, Marcus; Thomas, Clare; Jackson, Sue; Metcalfe, Chris; Kessler, David; Cramer, Helen
Abstract: The study aim was to assess implementation fidelity (i.e., adherence) to a talk-based primary care intervention using Conversation Analytic (CA) methods. The context was a UK feasibility trial where General Practitioners (GPs) were trained to use "BATHE" ( B ackground, A ffect, T rouble, H andling, E mpathy ) – a technique to screen for psychosocial issues during consultations – with frequently attending patients. 35 GPs received BATHE training between July–October 2015. 15 GPs across six practices self-selected to record a sample of their consultations with study patients at three and six months. 31 consultations were recorded. 21/26 patients in four intervention practices gave permission for analysis. The recordings were transcribed and initially coded for the presence or absence of the five BATHE components. CA methods were applied to assess delivery, focusing on position and composition of each component, and patients' responses. Initial coding showed most of the BATHE components to be present in most contacts. However the CA analysis revealed unplanned deviations in position and adaptations in composition. Frequently the intervention was initiated too early in the consultation, and the BATHE questions misunderstood by patients as pertaining to their presenting problems rather than the psychosocial context for their problems. Often these deviations resulted in reducing theoretical fidelity of the intervention as a whole. A CA approach enabled a dynamic assessment of the delivery and receipt of BATHE in situ revealing common pitfalls in delivery and provided valuable examples of more and less efficacious implementations. During the trial this evidence was used in top-up trainings to address problems in delivery and to improve GP engagement. Using CA methods enabled a more accurate assessment of implementation fidelity, a fuller description of the intervention itself, and enhanced resources for future training. When positioned appropriately, BATHE can be a useful tool for eliciting information about the wider context of the medical visit. Highlights: Talk-based methods are key to assessing fidelity in talk-based interventions. Conversation analytic methods can assess intervention delivery and receipt in situ . For success with BATHE, how and where it is delivered in the consultation matters. Real examples are key when training providers to change their communication habits.